Novel MAGFinFET: Operation, Design and Geometry Effect for Modern Sensors - Khine Thandar Nyunt Swe; Chanvit Pamonchom; Amporn Poyai; Toempong Phetchakul (My University, 2022)
This paper presents a new magnetic detection device, MAGFinFET, which is based on the advanced 3D FinFET structure. It can measure the vertical magnetic field by designing two contacts on both sides of the drain. The operation uses the principle of the current mode of Hall effect causing the deflection of the drain currents at both contacts. The 3D geometry effect was studied: channel length, fin height and fin width. It can be seen that when the values of these parameters are increased, the differential currents and relative sensitivities are increased linearly. Relative sensitivity has the highest value 0.00201 T−1-1 at channel length 50 nm. Fin height and fin width of 50 nm give the highest sensitivity of 0.00468 T−1-1 and 0.00415 T−1-1 respectively. Current density distributions of the different variations of each parameter Lgg, Fhh and Fww are observed by applying vertical magnetic field on the device. The 3D-MAGFinFET has been compared to that of the 2D non-split drain MAGFET structure and bulk fin resistor that use n-type semiconductor instead of induction channel. MAGFinFET shows quite higher sensitivity compared to bulk fin resistor. MAGFinFET mechanism models and simple characteristic equations are proposed in this work. Sentaurus TCAD is used for the device structure and simulation for the characteristics of MAGFinFET. This FinFET based device can be fabricated with modern integrated circuit technology.
Keywords: Fin; Hall effect sensor; Magnetic Field Sensors Techniques